Care management in thefamily health strategy: narrative review - Leite, Marinês Tambara; Nardino, Janaine; Hildebrandt, Leila Mariza; Santos, Adriane Marinês dos; Martins, Ricardo Vianna (Journal of Health Care, 2016)
Introduction: Health care management comprehends health service practices and demands reflections on new approaches to health care delivery, being included the one carried out by the Family Health Strategy (ESF). Objective: Analyze Brazilian publications in the period 2006-2013, related to health care management in ESF. Methodology: This is a narrative review whose bibliographic research was carried out in Health Virtual Library database (BVS-BIREME) and refined with LILACS database (Latin American and Caribbean Health Sciences Literature) and MEDLINE database (International Literature in Health Sciences). Results: From 73 articles found, after reading the abstracts 18 complied with inclusion criteria and were analyzed according the precepts of content analysis. The publications demonstrated the importance of management in ESF and indicated that professionals should make an effort to attend users’ and community’s needs, rendering quality services that generate satisfaction. Conclusion: The studies showed that there are fragilities in care provided by ESF and, thus, it is necessary to develop means to improve actions and interventions. Administrators are responsible for promoting knowledge and socialization, in order to achieve improvements in health care service and management qualification.